Associations between CD36 gene polymorphisms and susceptibility to coronary artery heart disease - Zhang,Y. (2014)
Associations between polymorphisms of the CD36 gene and susceptibility to coronary artery heart disease (CHD) are not clear. We assessed allele frequencies and genotype distributions of CD36 gene polymorphisms in 112 CHD patients and 129 control patients using semi-quantitative polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analysis. Additionally, we detected CD36 mRNA expression by real-time quantitative PCR, and we quantified plasma levels of oxidized low-density lipoprotein (ox-LDL) using an enzyme-linked immunosorbent assay (ELISA). There were no significant differences between the two groups (P>0.05) in allele frequencies of rs1761667 or in genotype distribution and allele frequencies of rs3173798. The genotype distribution of rs1761667 significantly differed between CHD patients and controls (P=0.034), with a significantly higher frequency of the AG genotype in the CHD group compared to the control group (P=0.011). The plasma levels of ox-LDL in patients with the AG genotype were remarkably higher than those with the GG and AA genotypes (P=0.010). In a randomized sample taken from patients in the two groups, the CD36 mRNA expression of the CHD patients was higher than that of the controls. In CHD patients, the CD36 mRNA expression in AG genotype patients was remarkably higher than in those with an AA genotype (P=0.005). After adjusted logistic regression analysis, the AG genotype of rs1761667 was associated with an increased risk of CHD (OR=2.337, 95% CI=1.336-4.087, P=0.003). In conclusion, the rs1761667 polymorphism may be closely associated with developing CHD in the Chongqing Han population of China, and an AG genotype may be a genetic susceptibility factor for CHD.